2003
DOI: 10.2190/kqpm-rj52-4uy6-9l1y
|View full text |Cite
|
Sign up to set email alerts
|

Motorcycle Taxis and Road Safety in Southwestern Nigeria

Abstract: Motorcycles have become a major form of commercial transportation in Nigeria over the past decade, due in large part to the economic downturn which has placed the purchase and maintenance of new cars and minibuses beyond the grasp of most. The phenomenon began in the towns of Igbo-Ora and Eruwa in southwestern Oyo State, Nigeria around 1989, and has been observed to have important health risks while at the same time providing essential transportation. The study documented 81 road traffic accidents from hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The older and experienced drivers were found to be more careful in observing road safety rules and practices than the younger and new drivers. The finding was in consonance with other previous studies, such as Williams (1999); Akinlade and Brieger (2004); Lafont, Amoros, Gadegbeku and Lawman (2009) and Okafor, Odeyemi and Dolapo (2013) who had earlier reported better road-safety practices among different group of drivers in their studies. The authors noted that older drivers were more careful to adhere to road-safety practices for prevention of road traffic accident.…”
Section: Discussion Of Findingssupporting
confidence: 93%
“…The older and experienced drivers were found to be more careful in observing road safety rules and practices than the younger and new drivers. The finding was in consonance with other previous studies, such as Williams (1999); Akinlade and Brieger (2004); Lafont, Amoros, Gadegbeku and Lawman (2009) and Okafor, Odeyemi and Dolapo (2013) who had earlier reported better road-safety practices among different group of drivers in their studies. The authors noted that older drivers were more careful to adhere to road-safety practices for prevention of road traffic accident.…”
Section: Discussion Of Findingssupporting
confidence: 93%
“…This "buy-in" strategy has been a success in some cities that were looking to create new street design guidelines (Mwebesa et al, 2021). Akinlade and Brieger (2003) also suggested that extending safety education and campaigns to the community through community leaders (religious and otherwise) would be beneficial in improving the road safety in South Western Nigeria. Zoning and exclusive are new strategies that may benefit from this method.…”
Section: Discussionmentioning
confidence: 99%
“…The popularity of motorcycle taxis has been increasing substantially recently, following the emergence of ride-hailing services such as GrabBike. Previous studies have showed high prevalence of crashes among traditional motorcycle taxi drivers [28,29]. Recently, Truong and Nguyen [30] found that ride-hailing motorcycle taxi drivers tended to have a greater risk of involvement in a mobile phone-related crash.…”
Section: Introductionmentioning
confidence: 99%